Ostensive Learning, Listener Behavior, and Function Transfer by Stimulus Pairing (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
Skinner defining verbal behavior in 1957 excludes the behavior of listener from this category, however, some authors such as Horne and Lowe and also Stemmer suggest that the behavior of listener can be a prerequisite for the acquisition of verbal behavior. Stemmer suggests that the behavior of listener is given by ostensive learning, a pavlovian learning that occurs by pairing of stimuli, and once acquired can be transferred to the behavior of speaker and differentially reinforced. This paper will suggest some simila-rities between the Stemmer’s approach to what Pavlov called Second Signal System, discussing empirical evidence on the function transference of stimuli in nonhumans and humans in the experimental literature. It will point out to the viability of the Pavlov and Stemmer’s theoretical approach to clarify the behavioral processes underlying the stimulus equivalence studies.
Keywords: verbal behavior; listener behavior; ostensive learning; pavlovian conditioning